2008
DOI: 10.1021/ja710206u
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Intermolecular Linear Allylic C−H Amination via Heterobimetallic Catalysis

Abstract: Nitrogen functionality is prevalent in synthetic and natural small molecules with significant biological activities. 1 Current state-of-the-art methods for installing nitrogen into complex organic frameworks generally proceed through oxygen. 2 While these methods feature high selectivities and predictable reactivities, they lengthen synthetic sequences by requiring unproductive chemical manipulations to install and maintain oxygen functionality. Reactions that selectively convert C-H directly to C-N stand to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(114 citation statements)
references
References 25 publications
2
110
0
2
Order By: Relevance
“…Although significant developments in aza-Wacker-type reactions have been achieved, the existing aza-Wacker process generally requires non-basic nitrogen nucleophiles such as carboxamides, carbamates, and sulfonamides as amination reagents, under relatively high oxygen pressures (4-10 atm.) or in the presence of an external oxidant source such as benzoquinone (BQ), PhBQ, PhI(OAc) 2 , or PhI(OPiv) 2 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In contrast, the oxidative amination of olefins using more basic, simple amines as substrates has been less explored, and is generally limited to intramolecular reactions [34][35][36][37][38], because of the strong coordination of amines to Pd, which results in catalyst deactivation.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although significant developments in aza-Wacker-type reactions have been achieved, the existing aza-Wacker process generally requires non-basic nitrogen nucleophiles such as carboxamides, carbamates, and sulfonamides as amination reagents, under relatively high oxygen pressures (4-10 atm.) or in the presence of an external oxidant source such as benzoquinone (BQ), PhBQ, PhI(OAc) 2 , or PhI(OPiv) 2 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In contrast, the oxidative amination of olefins using more basic, simple amines as substrates has been less explored, and is generally limited to intramolecular reactions [34][35][36][37][38], because of the strong coordination of amines to Pd, which results in catalyst deactivation.…”
Section: Open Accessmentioning
confidence: 99%
“…With regard to the reaction mechanism, it is known that η 3 -allylpalladium intermediates are formed by the reaction of alkenes with Pd(II) through allylic C-H bond activation [26,27,29]. To confirm the participation of the η 3 -allylpalladium intermediate as the key in the catalytic cycle, and in order to obtain further insights into the specific role of the Pd(OCOCF 3 ) 2 catalyst in this reaction, the (η 3 -cinnamyl)palladium trifluoroacetate dimer (7) and (η  -cinnamyl)palladium acetate dimer (8) were synthesized independently as model intermediates, according to the literature methods [61,62].…”
Section: (4)mentioning
confidence: 99%
“…31 Recently, a hetero-bimetallic Pd and Cr catalytic protocol has also been developed to affect a similar amination reaction. 27 We have proposed two possible mechanistic pathways (Fig. 4).…”
mentioning
confidence: 99%
“…Moreover, we have demonstrated that direct installation of nitrogen functionality from C—H bonds can have a powerful streamlining effect on synthetic routes. For example, the intermolecular C—H to C—N bond forming route to a rigidified (+)-deoxynegamycin analogue proceeded with five fewer steps, five fewer FGM, and a higher overall yield than the alternative C—O to C—N bond forming route 7. Despite this, the intermolecular allylic C—H amination reaction suffered from several limitations associated with the requirement for a Lewis acid activator [Cr(salen)Cl 2 ] to effect functionalization.…”
Section: Introductionmentioning
confidence: 99%